2008
DOI: 10.1158/1541-7786.mcr-07-0165
|View full text |Cite
|
Sign up to set email alerts
|

Decorin-Induced Growth Inhibition Is Overcome through Protracted Expression and Activation of Epidermal Growth Factor Receptors in Osteosarcoma Cells

Abstract: Decorin is an established natural oncosuppressive factor whose action is being studied in detail. Recently, decorin gene therapy formulations using adenoviral vectors have been shown in several animal models with very promising results. The present study describes the first exception to the established oncosuppression model using human osteosarcoma cells. MG-63 osteosarcoma cells were found to constitutively produce decorin, and furthermore, to be resistant to decorin-induced growth arrest. On the contrary, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…Collectively, these findings strongly correlate with the well established antitumor properties of decorin (88). Interestingly, the only exception to the established oncosuppression model is the case of the highly aggressive MG-63 human osteosarcoma cells, found to constitutively produce decorin and to be resistant to decorin-induced growth arrest (89).…”
Section: Roles In Bone Tumor Progressionsupporting
confidence: 69%
“…Collectively, these findings strongly correlate with the well established antitumor properties of decorin (88). Interestingly, the only exception to the established oncosuppression model is the case of the highly aggressive MG-63 human osteosarcoma cells, found to constitutively produce decorin and to be resistant to decorin-induced growth arrest (89).…”
Section: Roles In Bone Tumor Progressionsupporting
confidence: 69%
“…Decorin is normally present in the extracellular stromal compartment and analyses of various tumors indicate that it is rarely expressed by cancer cells. However, studies by us and others indicate that there are exceptions to this prevailing decorin expression and decorin mediated cancer growth and suppression model [21,26,27]. Ectopic decorin expression has been linked to increased vascular endothelial growth factor expression and increased angiogenesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Schematic representation of the major pathways that are employed for the decorin-mediated effects on PDGF-BB [31], TGFb [32], and EGF [33] functions. a recent study significant differences were identified between the decorin expression profiles of normal osteoblastic cells and osteosarcoma cells [26]. When analyzing the biological significance of this finding, new data emerged [26] which deviated from the established decorin-induced cytostatic pathway.…”
Section: Osteosarcoma Exceptionmentioning
confidence: 99%